STUDI LITERATUR SINTESIS MATERIAL METAL-ORGANIC FRAMEWORKS-5 (MOF-5) MENGGUNAKAN METODE SOLVOTERMAL DAN APLIKASINYA - Mid, Arsy Aprilia; Syaima, Husna; Hindryawati, Noor (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
This review article endeavours to comprehensively gather, compare, and scrutinize recent studies pertaining to the solvothermal synthesis of MOF-5 and its diverse applications. MOF-5 with the molecular formula Zn4O(BDC)3 which can be synthesized from a metal salt of zinc (Zn) with its organic ligands 1,4-benzene dicarboxylic acid (BDC) or terephthalic acid. In the last recent years, research on MOF-5 has continued to evolve and a variety of different synthesis methods have been tested. The synthesis process generally involves the use of polar organic solvents, such as N'N-diethylformamide (DEF) or N'N-dimethylformamide (DMF) at high temperatures and pressures. The solvothermal method is the most frequently used technique and allows good control over crystal size, morphology, and surface area. Factors such as solvent, temperature, reaction time, and metal/ligand ratio affect the properties of the resulting MOF-5 crystal. MOF- 5 is widely applied as a drug carrier material in drug delivery systems. MOF-5 has a high surface area that supports drug loading efficiency and significant hydrogen storage capacity. In addition, MOF-5's ability to release guest molecules in a controlled manner makes it an attractive choice for continuous applications. MOF-5 is also used in a variety of other applications including liquid and gas separation, catalysis, and adsorption. Research on modifying the structure of MOF-5 continues to evolve to meet the needs of increasingly diverse applications. Keywords : Synthesis, Terephtalic Acid, MOF-5, Solvothermal